LITERASI KEUANGAN DIGITAL UNTUK MENDORONG WIRAUSAHA BERBASIS DIGITAL - Nugroho Saputro; Muhammad Yusuf Indra Purnama; Linggar Ikhsan Nugroho; Muh Juan Suam Toro; Putra Pamungkas; Agista Putri Prameswari; Irwan Trinugroho (MANAJEMEN DEWANTARA, 2023)
Digital-based financial innovation has grown rapidly in recent times along with internet and smartphone penetration. The emergence of fintech and the existence of digital-based innovations carried out by incumbents in the financial services sector, in this case banking, are expected to increase financial inclusion. Furthermore, financial inclusion will encourage the growth of the real sector through increasing new entrepreneurs and also increasing the scale of existing micro and small businesses so that it will ultimately drive economic output growth. However, to achieve this goal, joint efforts are needed to increase the digital financial literacy of the community, especially the younger generation so that digital financial presence can be used for productive activities. This article discusses community service programs within the framework of developing digital financial literacy to encourage the growth of new entrepreneurs and increase the scale of existing micro and small businesses, especially by utilizing technology..